A study of urinary Bisphenol A levels in endocrine disorders - Kumar, Anupam; Verma, Rajesh; Agrawal, N. K. (International Journal of Research in Medical Sciences, 2018)
Background: Bisphenol A (BPA) is a very common endocrine disruptor. Traditionally high doses of BPA showed adverse effects with respect to organ failure and cancer. However, evidence now shows that doses well below the traditional toxicological threshold have metabolic effects. This observational study was aimed to measure the urinary levels of BPA among patients with endocrine disorders namely type 2 diabetes mellitus, hypothyroidism, non-obstructive azoospermia, polycystic ovarian syndrome (PCOS) and simple obesity, and to correlate urinary BPA levels with different clinical, biochemical and hormonal parameters. Methods: 30 newly diagnosed cases each of Type 2 diabetes mellitus, primary hypothyroidism, polycystic ovarian syndrome (PCOS), non-obstructive azoospermia and simple obesity were selected for study (single disorder in one patient). Age and sex matched healthy relatives of patients (n=30) were recruited as controls. All cases and controls were subjected to spot urinary BPA level estimation. Results: There were significant differences obtained in the median values of BPA in urine between cases of azoospermia, and simple obesity as compared to controls whereas no correlation was obtained between urinary BPA levels and BMI or waist hip ratio, in patients of type 2 DM and primary hypothyroidism. Urinary BPA was significantly lower than controls in cases of PCOS. Conclusions: Urinary levels of BPA are an indicator of its toxic effects especially in patients of non-obstructive azoospermia and simple obesity. The values of BPA in urine were widely distributed showing variability of exposure from the environment.